2018
DOI: 10.1007/s00296-018-4088-z
|View full text |Cite
|
Sign up to set email alerts
|

Acquired angioedema in juvenile systemic lupus erythematosus: case-based review

Abstract: An acquired form of angioedema that is clinically similar but scarcer than the hereditary form may be caused, even more rarely, by the presence of an underlying autoimmune disease. We report a previously healthy 16-year-old girl with an acquired angioedema as a rare and initial presentation of systemic lupus erythematosus. The patient had no previous angioedema attack and no family history. She did not have any chronic diseases and did not use any medicine regularly. The patient was diagnosed with systemic lup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…He demonstrated that the diagnosis of SLE and AE was concomitantly established for eight patients. 10 Seventeen patients were with low complement levels, five patients presented with glomerulonephritis, and three patients developed neuropsychiatric lupus. 10 Intriguingly, SLE patients found to have either low C1-INH 22 levels or high C1-INH autoantibodies 23 did not necessarily develop clinical AE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He demonstrated that the diagnosis of SLE and AE was concomitantly established for eight patients. 10 Seventeen patients were with low complement levels, five patients presented with glomerulonephritis, and three patients developed neuropsychiatric lupus. 10 Intriguingly, SLE patients found to have either low C1-INH 22 levels or high C1-INH autoantibodies 23 did not necessarily develop clinical AE.…”
Section: Discussionmentioning
confidence: 99%
“…Cacoub et al 9 described a "third type" of C1-INH-AAE in clinically quiescent SLE patients with transit low C1-INH antigenic and functional levels and hypocomplementemia, both of which normalized with resolution of AE after immunosuppressive therapy. Tekin et al 10 recently summarized 18 AAE cases associated with SLE. He demonstrated that the diagnosis of SLE and AE was concomitantly established for eight patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients presenting with angioedema crisis in the context of a disease such as SLE have improved with the administration of methylprednisolone pulses in 3 consecutive days in addition to maintenance therapy for the underlying disease [97].…”
Section: Acquired Angioedemamentioning
confidence: 99%
“…10 Angioedema can be a life-threatening condition for 15-33% SLE patients. 11 There shall be systematic and comprehensive handling management to reduce the ratio of mortality and morbidity in SLE emergency cases. However, in Indonesia, there are no guidelines or journals that explain about its treatment.…”
Section: Introductionmentioning
confidence: 99%